2011
DOI: 10.1590/s1807-59322011000100020
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between depression and apolipoproteins A and B: a case–control study

Abstract: OBJECTIVE:To investigate the relation between major depressive disorder and metabolic risk factors of coronary heart disease.INTRODUCTION:Little evidence is available indicating a relationship between major depressive disorder and metabolic risk factors of coronary heart disease such as lipoprotein and apolipoprotein.METHODS:This case–control study included 153 patients with major depressive disorder who fulfilled the criteria of the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM‐IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…An elevated plasma Apo-B level has been proposed to be a predictor of cardio-cerebrovascular events (Benn, 2009 ;Benn et al 2006 ;Sabino et al 2008 ;Walldius & Jungner, 2005 ;Walldius et al 2006). The finding of elevated plasma Apo-B levels in depressed patients is in accordance with previous studies (Sadeghi et al 2011 ;Sarandol et al 2006). However, it has also been reported that there is no significant difference in Apo-B levels between healthy controls and adults with elevated depressive symptoms (Lehto et al 2010).…”
Section: Discussionsupporting
confidence: 83%
“…An elevated plasma Apo-B level has been proposed to be a predictor of cardio-cerebrovascular events (Benn, 2009 ;Benn et al 2006 ;Sabino et al 2008 ;Walldius & Jungner, 2005 ;Walldius et al 2006). The finding of elevated plasma Apo-B levels in depressed patients is in accordance with previous studies (Sadeghi et al 2011 ;Sarandol et al 2006). However, it has also been reported that there is no significant difference in Apo-B levels between healthy controls and adults with elevated depressive symptoms (Lehto et al 2010).…”
Section: Discussionsupporting
confidence: 83%
“…SRM analysis revealed three apolipoproteins being changed in the TRM group comparison. A possible role of apolipoprotein changes during treatment of MDD has been suggested by previous studies (Sadeghi et al 2011;Hummel et al 2011).…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, lack of remission from depressive symptoms is also associated with low levels of both total serum cholesterol and LDL cholesterol [37,38]. In addition to the observed association with differing HDL and LDL levels, the levels of constituent apolipoproteins have been associated with MDD [39]. A case-control study revealed that depressed patients had higher circulating levels of LDL and its apolipoprotein B (apoB, constituent of LDL), alongside lower levels of HDL and apolipoprotein A (apoA, constituent of HDL) when compared to healthy controls.…”
Section: Cholesterolmentioning
confidence: 99%